Interpreting epidemiologic evidence strategies for study design and analysis - Savitz, David A. (New York ; Oxford : Oxford University Press, 2003)
Evaluating the strength of epidemiologic evidence is inherently challenging, both for those new to the field and for experienced researchers. This book offers a strategy for assessing epidemiologic research findings, explicitly describing the goals and products of research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epidemiology -- Technique